Direct taxation and the internal market: assessing possibilities for a more balanced integration - Yevgenyeva, Anzhela (University of Oxford, 2013)
The role of the Court of Justice of the European Union in the process of direct tax integration in the European Union (EU) has been widely discussed in the academic literature, while another important actor, the European Commission, has attracted much less attention. The Commission’s input is commonly perceived to be limited to the right of legislative initiative. This study questions such an oversimplified interpretation and draws a more nuanced picture of EU tax harmonisation by integrating an analysis of the complex regulatory approaches adopted by the Commission for the establishment and smooth functioning of the Internal Market. It is argued that the past decade brought a notable change in the Court-dominated pattern of direct tax integration. This change is apparent first in the evolution of enforcement strategies under Articles 258 and 260 TFEU; and second, in the increased reliance upon non-binding regulatory measures. Both developments have strengthened the role of the Commission, supplying it with more possibilities for influencing national direct tax systems, despite the reluctance of Member States to agree upon legislative harmonisation. Against this background, the procedural and substantive problems associated with these instruments require closer examination. The normative scope of this research covers the key procedural problems related to the infringement procedure and non-binding regulatory measures. The empirical component explores the Commission’s enforcement and coordination practices, drawing particular attention to two case studies: the tax treatment of losses in cross-border situations and exit taxation. Following the analysis of enforcement and coordination in the field of direct taxation, the study argues the need and proposes potential solutions for (i) the developing of a more comprehensive procedural framework for the infringement procedure and non-binding regulatory acts; (ii) the strengthening of accountability mechanisms; and (iii) the enhancing of the effectiveness of their application.
Keywords: Direct taxation; EU Law; Enforcement; European Law; Exit tax; Good governance; Infringement procedure; Internal Market; Non-binding coordination; Soft law; Tax coordination; Tax integration; Tax treatment of losses; Taxation